2021
DOI: 10.1111/febs.16059
|View full text |Cite
|
Sign up to set email alerts
|

Signaling pathways and defense mechanisms of ferroptosis

Abstract: As a type of lytic cell death driven by unrestricted lipid peroxidation and subsequent plasma membrane damage, ferroptosis occurs and develops because of sophisticated signals and regulatory mechanisms. The reactive oxygen species (ROS) used to initiate ferroptosis come from a variety of sources, including iron-mediated Fenton reactions, mitochondrial ROS, and membrane-associated ROS driven by the NOX protein family. Polyunsaturated fatty acid-containing phospholipids are the main substrates of lipid peroxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
136
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(158 citation statements)
references
References 131 publications
0
136
0
Order By: Relevance
“…For example, Wang et al (26) found that lycorine could target multiple myeloma stem cell-like cells through inhibition of the Wnt/β-catenin pathway. Liu et al (27) have investigated the proapoptotic effect of lycorine in hepatoblastoma HepG2 cells. These studies suggested that lycorine has an inhibitory effect on different cancer types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Wang et al (26) found that lycorine could target multiple myeloma stem cell-like cells through inhibition of the Wnt/β-catenin pathway. Liu et al (27) have investigated the proapoptotic effect of lycorine in hepatoblastoma HepG2 cells. These studies suggested that lycorine has an inhibitory effect on different cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…ACSL4 is considered to be the core regulatory gene of ferroptosis (27). The expression of ACSL4 in human RCC cells was significantly reduced compared with normal human renal cells (Fig.…”
Section: Determination Of Ferroptosis Levels In Human Rcc Cellsmentioning
confidence: 98%
“…Morphologically, ferroptosis is characterized by increased mitochondrial membrane densities and vanished mitochondrial cristae without obvious changes in nuclear morphology ( Cao and Dixon, 2016 ). The accumulation of ROS, depletion of GSH, inhibition of GPX4 activity, and increased release of polyunsaturated fatty acids (PUFAs) are regarded as the biochemical characteristics of ferroptosis ( Liu J. et al, 2021 ; Tang D. et al, 2021 ; Wu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Once excessive Fe 2+ is present in the labile iron pool, oxidative stress is induced by lipid peroxidation via the Fenton reaction catalysed by iron, resulting in a high sensitivity of cells to ferroptosis ( Cao and Dixon, 2016 ; Zhu et al, 2020 ). In addition to iron, genes regulating iron metabolic processes, such as haem oxygenase 1 (HO-1), also mediate the occurrence of ferroptosis ( Cao and Dixon, 2016 ; Liu J. et al, 2021 ). Another mediator, mitochondrial ferritin (FtMt), an iron-storage protein located in the mitochondria that plays a significant role in modulating cellular iron metabolism, has been demonstrated to protect cells from erastin-induced ferroptosis ( Wang P. et al, 2021 ; Wang X. et al, 2021 ; Wang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…inevitably leads to cell death. [26][27][28] Ferroptosis is confirmed to be caused by the iron-dependent accumulation of ROS, which provides a novel mechanism for the prevention of tumor development. 29 Recent studies on HSPB1, 13,30 which could serve as an important regulator in the ferroptotic process of tumor cell death, have provided promising insights into the mechanism of ferroptosis, as well as a theoretical foundation for combinational therapy targeting both HSPB1 and ferroptosis.…”
mentioning
confidence: 99%